2013
DOI: 10.1016/j.biomaterials.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

An electrospun scaffold integrating nucleic acid delivery for treatment of full-thickness wounds

Abstract: We developed a multi-functional construct capable of controlled delivery of bioactive substances that can improve wound repair by supporting the intrinsic ability of the skin to heal. We synthesized electrospun scaffolds—composed of a blend of the degradable polymers poly(L-lactide) (PLA) or polycaprolactone (PCL)—that produce highly efficient non-viral in vivo gene delivery to cells in the wound bed, provide a protective barrier during early wound healing, and support cell migration and growth. This multi-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 38 publications
(43 reference statements)
2
59
0
Order By: Relevance
“…Both meshes showed similar and low levels of fibrosis. These results were consistent with reports of biocompatibility of electrospun PCL-based meshes [47,48]. Notably, there was no perturbation of surrounding subcutaneous tissues and subjacent muscle that was observed in the injecton controls (Figure S5–S6).…”
Section: Resultssupporting
confidence: 91%
“…Both meshes showed similar and low levels of fibrosis. These results were consistent with reports of biocompatibility of electrospun PCL-based meshes [47,48]. Notably, there was no perturbation of surrounding subcutaneous tissues and subjacent muscle that was observed in the injecton controls (Figure S5–S6).…”
Section: Resultssupporting
confidence: 91%
“…Electrospinning is the process of forming nanofibers by applying electric charge to a viscoelastic suspension such that electrostatic force becomes greater than surface 38 The diameter and size of the fibers can be controlled by changing the viscosity, temperature, feed rate, conductivity, voltage, size of orifice and distance between capillary and collector. 39 Zhuang et al have synthesized gelatin/chitosan/silver nanofibers in the diameter range of 220-400 nm which Dermal Tissue Engineering 7…”
Section: Electrospinningmentioning
confidence: 99%
“…Early epithelialization was observed in case of Group 2 compared to control untreated rats, which provide a barrier to fluid and electrolyte loss and prevent infections. 123 From the routinely stained hematoxylin and eosin sections, it was found that inflammatory phase of Group 1 rats was prolonged compared to Group 2 rats. In case of Group 1 rats, the level of inflammation was amplified on day 3 compared to Group 2 rats (Fig.…”
Section: In Vivo Analysismentioning
confidence: 98%